(untitled) (Journal of Asian Development Studies, 2026)
This study empirically estimates the impact of economic globalization and mobility of labor on inclusive growth in Pakistan. To achieve inclusive growth is crucial for economies because that brings equal formation of opportunities and their access to everyone through participating in growth process. Economic globalization would stimulate the process of development in developing countries by reducing gap in techniques of production and enhancing exports, generating employment opportunities, declining the poverty ratio rather than creating jobless growth in developing countries. Labor force rapidly increasing in developing countries such policies that help to augment globalization process in positive way via increasing mobility of skilled labor to developed countries the target of inclusive growth could be achieved in developing countries like Pakistan. There exist few studies which indicate the globalization and labor mobility important variable for inclusive growth with positive effects on developing countries. In this study economic globalization, WRI, government spending on health, female to male labor force participation rate, political globalization, trade, FDI and inflation will be treated as independent variables whereas, real per capita income will be treated as dependent variable proxy for inclusive growth. Time series data will be used span from 1982 to 2016. Before applying any empirical technique for confirmation of results the preliminary step is to check stationarity of data by using ADF. The findings of the study show there is positive effect of economic globalization, FDI, trade, PG, WRI, inflation, F/M LFP on inclusive growth in Pakistan in the intervening time1982-2016. Policy implications for the study are government should put serious emphasis on target and achieving inclusive growth through allow economic globalization and in the country. More skilled people should be mobile between countries which will bring more revenue and will play a vital role in economic growth to enhance GDP per capita.